The Adventures of a Japanese Monk in Colonial Korea: Sōma Shōei's Zen Training with Korean Masters - Kim, Hwansoo Ilmee (Japanese journal of religious studies, 2009)
The Japanese Buddhist view of Korean Buddhism from 1877 to 1945 abounded with colonialist and imperialistic rhetoric. Japanese Buddhist missionaries declared that Korean Buddhism should be reformed and revitalized under their guidance. With this mindset, most Japanese Buddhists in colonial Korea did not find much in Korean Buddhism that was useful or worth learning about-a paternalistic approach that Korean monks found off-putting and that therefore undermined potential cooperation. This paper introduces an unusual Japanese priest who spent six years practicing Sŏn (Jp. Zen) in Korean monasteries. Sōma Shōei's identity as an unsui (itinerant monk)-a monastic class shared across the Buddhisms of East Asia-enabled him to develop friendships with Korean Sŏn masters and fellow practitioners, relationships that were framed less by colonialist or nationalist discourse than by respect, empathy, and sincerity. This article presents Sōma's firsthand experience with Korean monasticism based on essays he wrote for a Japanese Buddhist journal. Soma's case reveals how religious identity operates within and also beyond the colonial context. Sōma's exceptionalism also provides a contrast to the views of his colleagues, which helps reveal greater complexity in the ways that Japanese Buddhists thought about Korean Buddhism.